The linburg-comstock anomaly: incidence in Malaysians and effect on pinch strength - Low, T.H.; Faruk Senan, N.A.; Ahmad, T.S. (2012)
To obtain epidemiologic data of the linburg-comstock anomaly in malaysia and to study the effect of the anomaly on key pinch strength. Methods: We examined 292 healthy subjects (162 female and 130 male) bilaterally for the presence of the linburg-comstock anomaly. Each subject's key pinch strength was measured bilaterally using a pinch meter. Results: The linburg-comstock anomaly was present in 101 of the 292 subjects (35%). Sixty-five subjects (22%) had it unilaterally, and 36 subjects (6%) had it bilaterally. The anomaly was associated with superior key pinch strength. Conclusions: The study provides epidemiologic data of this anomaly in malaysia and considers its anatomical influence on key pinch strength. Type of study/level of evidence: Prognostic iv.